Helicoidal surfaces of finite type in the 3-dimensional Heisenberg group. Issue 4 (19th May 2022) - Senoussi, Bendehiba
Abstract: An Euclidean submanifold is said to be of finite Chen-type if its coordinate functions are a finite sum of eigenfunctions of its Laplacian [6]. In this article, we study helicoidal invariant surfaces in the 3-dimensional Heisenberg group H 3, which has finite type immersion.